Design of steel channel tension members-proposal to IS 800:2007 - Priya, C. Bharathi; Keerthana, M.; Verma, Mohit; Banjara, Nawal Kishor (Journal of Structural Engineering, 2024)
Steel tension members are commonly used in bracing members, chords and web members of trusses, in which not all the elements of the cross section are connected to the gusset plates. The most commonly used cross sections for tension are angles and channels. These sections are connected only through one leg due to which the unconnected elements suffer a ’shear lag’ compared to the connected legs. Hence, the whole section is not effective in resisting the tension. The formula given in IS 800:2007 for angle sections is generally used for the design of channel sections taking analogous dimensions. The objective of the present investigation is to study the adequacy of the present IS: 800 formula for channels and accordingly propose new design equation. Experimental investigations and provisions of other international codes for channel tension members are taken as basis to critically examine the design provisions of IS: 800.